Effect of process parameters on WEDM of Al – Fly ash composites using Taguchi Technique. (2021) - Ananth, S.; Udaya Prakash, J.; Jebarose Juliyana, S.; Sarala Rubi, C.; Divya Sadhana, A.
Abstract: In this modern era, in some aspects of our lives, we all rely on composite materials. Aluminum matrix composites (AMCs) consist of aluminium alloy (LM6) as matrix and 3, 6 and 9 percentage of particulate fly ash as reinforcement material was manufactured by the Stir casting process. WEDM trials were performed on AMCs using Taguchi Technique implementing the L27 orthogonal array. The influence of process parameters on MRR was investigated using S/N analysis. Analysis of variance (ANOVA) was carried out to analyse the importance of the input parameters concerning the basic features of the WEDM mechanism and the contribution of the process parameters. Confirmation experiments were conducted to confirm the enhancement of the determined values with the optimum combination. Gap Voltage (62.98%) has the largest statistical influence on composite MRR led by Pulse off Time (17.25%) and Pulse on Time (16.67%).